Environmental variables affecting the gillnet catches and condition of Labiobarbus Festivus and Osteochilus Hasseltii in northern Malaysia - Rahman, Mohammad Mustafizur; Fathi, Ahmad; Broadhurst, Matt K. (KeAi Communications Co., 2021)
The influences of technical factors on the catching efficiencies of gillnets are well understood, but less is known about the importance of environmental factors and how these might concurrently affect target-species condition. Here we address this deficit for two economically important southeast Asian cyprinids (Labiobarbus festivus and Osteochilus hasseltii) during a one-year study at a key fishing location in Lake Kenyir, Malaysia. Three gillnets (each 200 m long, 2 m deep and comprising either 38-, 51-, or 76-mm mesh) were deployed each month concurrent with sampling of benthic macroinvertebrates and various environmental parameters. Various multivariate analyses (detrended correspondence analysis, redundancy analysis and permutational multivariate analysis of variance) were used to explore potential relationships between the extrinsic variables (mesh size, sampling season, water quality and, based on known prey items, benthic macroinvertebrates) and gillnet catches and the biological condition (growth co-efficient and hepatosomatic index) of the target species. Catches of L. festivus (the most abundant species) were positively influenced by water turbidity without seasonal effects, while their biological condition was positively influenced by benthic macroinvertebrates (mostly Trichoptera) and the concentrations of DO and phosphate, and negatively influenced by water temperature. By comparison, seasonal influences on the catches and biology of O. hasseltii were somewhat size specific with positive and negative effects of the monsoon on small and large fish, respectively. The abundance of phytoplankton also positively affected the catches of O. hasseltii, while their biological condition was positively influenced by water temperature, but negatively influenced by water turbidity. Such species-specific differences were attributed to life histories, and although the more abundant L. festivus might be best sought during any period of turbidity, effort should be focused during the monsoon when individuals have optimal condition (and therefore better flesh quality). In contrast, larger O. hasseltii might be best sought during non-monsoon months concurrent with greater catches and optimal condition. Collecting similar data for other freshwater species both nationally and internationally might facilitate future efforts at fine-tuning gillnet fishing effort.